Transcriptions and Cognitive Perceptions of Zakāt in the French Literature (1660-2017): What Can We Learn? - Abderrazak Belabes (International Journal of Zakat, 2017)
The aim of this study is to explore the different transcriptions and cognitive perceptions of the notion of Zakāt in French literature from 1660 to 2017. The study lists twenty-three transcriptions and thirty-two cognitive perceptions. Most interpret it in their own way, according to their experiences, their feelings, and the time devoted to its knowledge, although scholarly literature is not lacking. This highlights the importance of the Orwell’s problem: How is it that human beings know so little when they have access to so much knowledge? Hence the need to differentiate, beyond the essentialization of others, between the existence of the object, its representation, and the way to arrive at its knowledge. Zakat is not merely a technical question, it embodies a vision of the life in society where money is not an end; it is a means for a higher purpose. Keywords: Zakāt , transcription, cognitive perception, French literature JEL Classification Code: B40, H20, P50, Z12